Waqf management and accountability: Waqf land financing models for economic wellbeing - Priyadi, Unggul; Achiria, Siti; Imron, Mochamad Ali; Zandi, Gholam Reza (Asian Economic and Financial Review, 2023)
Waqf land can be a factor in the economic wellbeing of the community if it is managed productively. At the same time, it is necessary to determine the best financing model to manage waqf land because waqf institutions are constrained by the absence of funds to produce waqf assets. This paper aims to describe the financing models that can be applied in the development of productive waqf land, as well as find the most effective financing model for productive waqf land. Financing that reduces the risk of loss needs to be considered by waqf institutions in choosing the right financing model. Waqf management aims to properly run and increase the waqf properties’ value while fostering the culture of waqf for the good of the community. In most Muslim nations, the government is in charge of overseeing the management of waqf properties to varying degrees. However, communities have built-in claims on the issues that affect them, including the usage of waqf properties. Therefore, in every activity, including the management of waqf, are all for the sake of Allah (lillahi ta’ala).